Resposta glicêmica e perfil de saciedade de sobremesa à base de plantas e sua conversão em produto em pó obtido por atomização - Pereira, Maria Tereza Lucena (2025)
The demand for plant-based foods is growing due to environmental issues and the correlation with positive health outcomes, such as glycemic control and promotion of satiety. This scenario has driven the development of innovative products that reconcile nutritional quality, practicality and versatility. In this context, spray drying emerges as a promising alternative to obtain powdered foods that meet these attributes. Therefore, the objective of this study was to evaluate the glycemic response (GR) and satiety in adult individuals after the consumption of a plantbased dessert (SBP), in addition to optimizing its formulation and converting it into a powdered product (PEP) obtained by atomization. In the first stage, a randomized crossover pilot study was conducted with eleven participants, who consumed SBP, an equivalent commercial milk dessert (SLC), and a standard glucose solution. Capillary blood glucose was monitored for 120 minutes to assess GR, and visual analog scales were applied to measure subjective satiety. Glucose induced a significantly higher GR (p<0.05) than that of SBP at 15, 30, 45, 60 and 90 minutes, and that of SLC at 30, 45 and 60 minutes. The SBP, in turn, promoted an inferior GR (p<0.05) (94.50±9.36 mg/dL) to that of the CFS (101.59±11.40 mg/dL) at 90 minutes, suggesting an earlier return to baseline glucose levels. The incremental area under the glycemic curve was also significantly higher (p<0.05) for the glucose solution (16209±1052 mg·min/dL) compared to SBP (13003 ± 466 mg·min/dL) and SLC (13492 ± 492.2 mg·min/dL). In addition, SBP was more effective in promoting more satiety at 90 and 120 minutes and lower appetite at 60, 90 and 120 minutes, compared to SLC. After consuming SBP, participants also showed less interest in salty or savory foods. In the subsequent stage of the study, SBP was improved and reconstituted in a solution containing distilled water and 10% adjuvants (maltodextrin or pea protein), resulting in twelve formulations. These were subjected to spray drying under predetermined conditions. The M4 formulation, with 60% dilution and the addition of 10% maltodextrin, showed the best yield (40.01%) and, therefore, was selected for physicochemical characterization. The PEP obtained showed reduced moisture (2.81%) and Aw (0.24%), high carbohydrate (91.37%) and fiber (6.69%) content, low lipid content (1.46%), reduced energy density (119.91 kcal/100g) and high antioxidant activity (99.36%). Additionally, it demonstrated non-hygroscopic characteristics (5.0%), acceptable solubility (52.29%), fast rehydration time (34.57 seconds) and reduced bulk density (0.40 g/mL). X-ray analysis revealed that PEP has an amorphous structure, while Nuclear Magnetic Resonance spectroscopy identified the presence of carbohydrates (maltotetraose and sucrose), essential amino acids (with a predominance of threonine) and organic acids. In summary, the results obtained showed that SBP has positive effects mainly on satiety and the modulation of food cravings, as well as confirmed the technological feasibility of its conversion into a PEP. This, in turn, presented promising nutritional and technological properties, in addition to high market potential